Platelets’ morphology, metabolic profile, exocytosis, and heterotypic aggregation with leukocytes in relation to severity and mortality of COVID-19-patients - Yasseen, Basma A.; Elkhodiry, Aya A.; El-Messiery, Riem M.; El-sayed, Hajar; Elbenhawi, Malak W.; Kamel, Azza G.; Gad, Shaimaa A.; Zidan, Mona; Hamza, Marwa S.; Al-ansary, Mohamed; Abdel-Rahman, Engy A.; Ali, Sameh S. (Frontiers in Immunology, 2022)
modulate innate immune cells. Leukocyte-platelet aggregations and activation-induced secretome are among factors recently gaining interest but little is known about their interplay with severity and mortality during the course of SARS-Cov-2 infection. The aim of the present work is to follow platelets’ bioenergetics, redox balance, and calcium homeostasis as regulators of leukocyte-platelet interactions in a cohort of COVID-19 patients with variable clinical severity and mortality outcomes. We investigated COVID-19 infection-related changes in platelet counts, activation, morphology (by flow cytometry and electron microscopy), bioenergetics (by Seahorse analyzer), mitochondria function (by high resolution respirometry), intracellular calcium (by flow cytometry), reactive oxygen species (ROS, by flow cytometry), and leukocyte-platelet aggregates (by flow cytometry) in non-intensive care unit (ICU) hospitalized COVID-19 patients (Non-ICU, n=15), ICU-survivors of severe COVID-19 (ICU-S, n=35), non-survivors of severe COVID-19 (ICU-NS, n=60) relative to control subjects (n=31). Additionally, molecular studies were carried out to follow gene and protein expressions of mitochondrial electron transport chain complexes (ETC) in representative samples of isolated platelets from the studied groups. Our results revealed that COVID-19 infection leads to global metabolic depression especially in severe patients despite the lack of significant impacts on levels of mitochondrial ETC genes and proteins. We also report that severe patients’ platelets exhibit hyperpolarized mitochondria and significantly lowered intracellular calcium, concomitantly with increased aggregations with neutrophil. These changes were associated with increased populations of giant platelets and morphological transformations usually correlated with platelets activation and inflammatory signatures, but with impaired exocytosis. Our data suggest that hyperactive platelets with impaired exocytosis may be integral parts in the pathophysiology dictating severity and mortality in COVID-19 patients.